Perceived Factors Affecting Patient Disclosure on Matters Concerning Contraception and Sexual History in Young Adults in Bengaluru, Karnataka - Shirin Laturkar; Andrea Neha Dias; Vanshikha Agarwal; Anand Dattatreya Meundi (Indian Journal of Public Health, 2025)
Background: In India, cultural norms imply that premarital sex rarely occurs. These beliefs contrast sharply with an increase in permissiveness toward premarital sex and the possibility of unprotected, risky sexual behavior. Young adults may hesitate to discuss their sexual history and contraceptive concerns with doctors, resulting in adverse reproductive health outcomes. Understanding the factors affecting a patient’s decision to withhold, this history could help improve the state of sexual health among young adults in India. Objectives: The objectives of this study were to assess attitudes and perceptions regarding the disclosure of information about sex and contraception when seeking health care and to identify perceived factors affecting the disclosure of information about sex and contraception among young adults in Bengaluru when they seek health care. Materials and Methods: Following a pilot study, 60 participants were selected from four colleges in Bengaluru (multistage random sampling). A digital questionnaire was administered. Results: Of the 60 respondents (aged 18–25), 22 (36.7%) were sexually active. Fifteen (25%) respondents did not consider themselves adequately knowledgeable regarding contraceptives. The majority of respondents considered the Internet to be their main source of information regarding contraceptives but considered health-care providers to be the most reliable. Unprofessional physician behavior, the presence of parents/guardians in the room, and the existence of a personal relationship between the physician and the patient’s family would likely result in respondents withholding sexual history. Conclusion: Young adults consider health-care providers reliable sources of contraceptive knowledge, yet rarely utilize them. Physicians must take steps to maintain a favorable environment to encourage young adults to disclose their sexual history.